2019
DOI: 10.1017/cts.2019.368
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled pilot study of the University of Minnesota mentoring excellence training academy: A hybrid learning approach to research mentor training

Abstract: Introduction:Research mentor training is a valuable professional development activity. Options for training customization (by delivery mode, dosage, content) are needed to address the many critical attributes of effective mentoring relationships and to support mentors in different institutional settings.Methods:We conducted a pilot randomized controlled trial to evaluate a hybrid mentor training approach consisting of an innovative, 90-minute, self-paced, online module (Optimizing the Practice of Mentoring, OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
(41 reference statements)
0
16
0
3
Order By: Relevance
“…Smaller institutions such as startups, on the other hand are working to provide environments where mentoring will thrive organically [ 7 ]. The structured mentoring program is currently regarded as the gold standard in mentoring because the mentor is first trained to mentor which then results in improvement of their mentoring knowledge, skills, and demeanors at mentoring [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smaller institutions such as startups, on the other hand are working to provide environments where mentoring will thrive organically [ 7 ]. The structured mentoring program is currently regarded as the gold standard in mentoring because the mentor is first trained to mentor which then results in improvement of their mentoring knowledge, skills, and demeanors at mentoring [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study of STEM mentor training, mentors who received training about issues of diversity in STEM were more likely to discuss these issues with their mentees compared with mentors who did not receive training 46 . A randomized trial of blended online and in‐person training for faculty STEM mentors reported that mentors who completed the training program had greater knowledge and skills than mentors in the no training group 47 . These studies provide support for the effectiveness of mentor training for influencing mentors’ knowledge, attitudes, and skills to prepare them to mentor.…”
Section: Introductionmentioning
confidence: 83%
“…as one of the Mentored Career Development and NRSA Training Review Criteria. To be responsive, training hubs are implementing a variety of trainings, such as seminars and evidence-based workshops, across various platforms (in-person, online synchronous, and online asynchronous) [20][21][22]. As noted in the survey responses, some CTSA programs have established comprehensive mentoring academies to provide resources for their health sciences faculty [23][24].…”
Section: Discussionmentioning
confidence: 99%